The Secret in the Hills - Lewis, David, 1932- (Elgin, Ill. : Chariot Books, 1979)
A recently-orphaned boy tries to adjust to his new life with his relatives and to save the life of a blind mine pony.
Keywords: Orphans -- Fiction; Ponies -- Fiction; Coal mines and mining -- Fiction; Wales -- Fiction